9(4x+8)=12(12+3x)

Simple and best practice solution for 9(4x+8)=12(12+3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(4x+8)=12(12+3x) equation:


Simplifying
9(4x + 8) = 12(12 + 3x)

Reorder the terms:
9(8 + 4x) = 12(12 + 3x)
(8 * 9 + 4x * 9) = 12(12 + 3x)
(72 + 36x) = 12(12 + 3x)
72 + 36x = (12 * 12 + 3x * 12)
72 + 36x = (144 + 36x)

Add '-36x' to each side of the equation.
72 + 36x + -36x = 144 + 36x + -36x

Combine like terms: 36x + -36x = 0
72 + 0 = 144 + 36x + -36x
72 = 144 + 36x + -36x

Combine like terms: 36x + -36x = 0
72 = 144 + 0
72 = 144

Solving
72 = 144

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| h=-16t^2+1000 | | 32=6(x+4)-8x | | (3x+4)+(2x+2)= | | 8+5(7+5n)=193 | | 2.5x+1.96=1.7x+2.92 | | w+6-13=-27 | | 3(5x+4)=31 | | 3x+2(5)=0.2(2y+1) | | 45+5.50x=195+4.25x | | -x+3(-x+8)=0 | | 3+4+a=12 | | (C+5)+(c-1)=90 | | 4y+6(y+8)= | | 3(x+1)+4x=24 | | 18.1--0.7=c | | 75c^2+90cd+27d^2= | | 18.1--0.7= | | 16x^2-38x-5= | | 9=-7y+8 | | y=(3)(-1)-2 | | 79=8x-11 | | 5m-8.5=3.7m+4.37 | | 16x^2-38c-5= | | 2m^2-29m+60=0 | | y=(3)(1)-2 | | 1.5x+.7=10.7+.5x | | 7x+6=8-(7x-6) | | -2(5k-1)=22 | | 5n+7+7=3n-2+2(2n+1) | | y=(3)(0)-2 | | 5y-81x=0 | | 50x+6=6+50x |

Equations solver categories